Fundações privadas: do poder à responsabilidade dos dirigentes - Grazzioli, Airton (2011)
Analytical approach about the experience resulted from the performance of duties of the Guardians of Foundations in the capital São Paulo, in charge of approximately 3 hundred private foundations, most of them with expressive social activity and significant assets, which provide automatically an opportunity of dealing with relevant daily matters. It was performed systematic development about concepts and specificity of private foundations, as invidious who are part of the Tertiary Sector. It was made registration information surveys with Attorney General‟s office of São Paulo, where it has shown how significant the social work developed by these entities is, for the society‟s benefit, as well as the billionaire capital they amass, which works as a sign for the importance of studies of the leaders‟ responsibilities. Thesis on its managing performance, power engagement of the duties and responsibilities of the administrators of the foundations. Critical analysis of lack of specific legal standards for the civil responsibilities and Criminal responsibilities of the private foundations leader, who manage the civil society‟s interests